Asuhan Keperawatan Pada Tn. S Dengan Diabetes Melitus Tipe II Di Ruangan Mina Rumah Sakit Aisyiyah Pariaman - Rizatul Aini; Mike Asmaria; Debby Silvia Dewi; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to the International Diabetes Federation (IDF), the number of people with diabetes worldwide in 2021 was around 537 million. In Indonesia, around 19.5 million adults were recorded as having diabetes in 2021. In West Sumatra, the number of cases of type II diabetes was recorded as 245,105 in 2018, representing 13.725%. Data yang diperoleh dari kasus diabetes mellitus di RS Aisyiyah Pariaman pada tahun 2024 adalah 278 kasus, menempati urutan keempat untuk jumlah kasus penyakit terbanyak. The aim of this scientific paper is to provide nursing care for patients with type II diabetes mellitus, including assessment, diagnosis, intervention, implementation, evaluation and documentation. The study was conducted as a case study with one patient in Room Mina at RS Aisyiyah Pariaman from 19 to 23 September 2025. The results of the study revealed the following nursing problems: unstable blood glucose levels, impaired skin integrity, risk of infection, and risk of nutritional deficiency. The results of the evaluation and implementation show that the problems of unstable blood glucose levels, impaired skin integrity, risk of infection and risk of nutritional deficiency were resolved by day 5. It is hoped that through this study, patients and their families will be able to provide care and maintain a healthy diet and lifestyle, as well as adhere to their medication, thereby preventing other family members from developing type II diabetes.